Effect of Cholesterol on Membrane Fluidity and Association of Aβ Oligomers and Subsequent Neuronal Damage: A Double-Edged Sword - Fernández-Pérez, Eduardo J.; Sepúlveda, Fernando J.; Peters, Christian; Bascuñán, Denisse; Riffo-Lepe, Nicolás O.; González-Sanmiguel, Juliana; Sánchez, Susana A.; Peoples, Robert W.; Vicente, Benjamín; Aguayo, Luis G. (Frontiers in Aging Neuroscience, 2018)
Background: The beta-amyloid peptide (Aβ) involved in Alzheimer's disease (AD) has been described to associate/aggregate on the cell surface disrupting the membrane through pore formation and breakage. However, molecular determinants involved for this interaction (e.g. some physicochemical properties of the cell membrane) are largely unknown. Since cholesterol is an important molecule for membrane structure and fluidity, we examined the effect of varying cholesterol content with the association and membrane perforation by Aβ in cultured hippocampal neurons. Methodos: To decrease or increase the levels of cholesterol in the membrane we used methyl-β-cyclodextrin (MβCD) and MβCD/cholesterol, respectively. We analyzed if membrane fluidity was affected using generalized polarization (GP) imaging and the fluorescent dye di-4-ANEPPDHQ. Additionally membrane association and perforation was assessed using immunocytochemistry and electrophysiological techniques, respectively. Results: The results showed that cholesterol removal decreased the macroscopic association of Aβ to neuronal membranes (fluorescent-puncta/20 µm: control =1 8±2 vs. MβCD = 10±1, p<0.05) and induced a facilitation of the membrane perforation by Aβ with respect to control cells (half-time for maximal charge transferred: control=7.2 vs. MβCD=4.4). Under this condition, we found an increase in membrane fluidity (46 ± 3.3% decrease in GP value, p<0.001). On the contrary, increasing cholesterol levels incremented membrane rigidity (38 ± 2.7% increase in GP value, p<0.001) and enhanced the association and clustering of Aβ (fluorescent-puncta/20µm: control= 18±2 vs. MβCD= 10±1, p<0.01), but inhibited membrane disruption. Conclusions: Our results strongly suggest the importance of plasma membrane organization in the toxic effects of Aβ in hippocampal neurons, since fluidity can regulate the distribution and insertion of the Aβ peptide in the neuronal membrane.